Simulation study on the frequency modulation of sawtooth oscillation by plasma shape in tokamak - Zhang, Peijie; Yang, Jinhong; Ren, Zhenzhen; Xiao, Zheng; Chu, Jiaxuan; Kuang, Jun; Wang, Weihua (Nuclear fusion, 2025)
This study numerically investigates the impact of the tokamak plasma shape (elongation, triangularity, and aspect ratio) on the amplitude and period of sawtooth oscillations using the three-dimensional toroidal nonlinear magnetic fluid code CLT and the simulation results are qualitatively compared with the experimental observation in Tokamak Configuration Variable. The study reveals a frequency modulation phenomenon for the sawtooth period with respect to the elongation and aspect ratio. (1) The simulation results of the sawtooth linear phase show that a large elongation and a positive triangularity are beneficial for the stability of the internal kink mode, while a negative triangularity has limited effect on the stability of the internal kink mode. (2) The simulation results of the sawtooth oscillation phase show that the sawtooth period generally increases with the increase of elongation. However, when the elongation is relatively small, there is a significant peak in the sawtooth period, and this peak position is modulated by elongation and aspect ratio. Analysis suggests that the peak of the sawtooth period is caused by the occurrence of m / n = 3/2 mode during the sawtooth crashes. (3) The sawtooth period exhibits a monotonic increasing relation with the triangularity, while the sawtooth amplitude increases with both the elongation and triangularity.